Effect of audit committees' compositions on the financial performance of selected South Africa State-Owned Enterprises - Nchabeleng, Olga Peloane (My University, 2019)
The apparent weaknesses in corporate governance of state-owned enterprises and poor audit reports have heightened the concern of investors and the state as the major shareholder of these enterprises returns. Audit committees as a mechanism for good corporate governance plays a major role in enterprise performance. These state-owned enterprises play a vital role in the economy of South Africa. This study examines the effect of audit committee composition (independence, gender diversity, financial expertise and size) on financial performance measured by return on assets using major state-owned enterprises listed on Schedule 2 of PFMA. The results show that the audit committee size, gender diversity and financial expertise has an insignificant positive relationship with ROA, whereas the independence of audit committee members has an insignificant negative association. The result of the study may be beneficial to various stakeholders and boards of enterprises to make some proper decisions on audit committee composition to attract more investors and at the same time safeguarding the investments of shareholders.
Thesis M.COM. (Accounting)) -- University of Limpopo, 2019
Keywords: Corporate governance; Audit committee; Enterprise performance; Audit committees -- South Africa; Corporations -- Auditing; Government business enterprises -- South Africa; Corporate governance -- South Africa; Corporations -- South Africa -- Finance